Development of the E-KSPR Telemedicine Application for Screening Pregnancy Risk Factors to Prevent Maternal Mortality - Nahdiyah Karimah; Entan Afriannisyah (YCAB Publisher, 2026)
Background: In 2023, the global maternal mortality rate (MMR) reached 197 per 100.000 live births. Most maternal deaths caused by complications are preventable through early detection. The Poedji Rochjati Score Card (KSPR) serves as a widely used screening tool in Indonesia for detecting high-risk pregnancies. However, users may still miscalculate the KSPR score. To minimize errors in completing the conventional KSPR, developers created the E-KSPR Telemedicine application. This tool includes online chat features, explanations of follow-up actions based on score results, and accessibility for both clients and family members. Objective: This study aimed to develop the E-KSPR Telemedicine application to screen risk factors in pregnant women as a preventive measure against maternal mortality. Methods: This research and development (R&D) study developed a web-based E-KSPR Telemedicine application. The study took place from June 24 to July 31, 2024, at Sangkrah Public Health Center. A total of 94 respondents who met the inclusion and exclusion criteria participated. The study used the User Experience Questionnaire (UEQ) to evaluate the application. Researchers analyzed the evaluation results using the UEQ Data Analysis Tool Version 12. Results: The E-KSPR Telemedicine application scored an average above 2.5 across all UEQ scales, indicating that respondents generally had a highly positive perception. Reliability coefficients using Cronbach’s Alpha and Guttman’s Lambda2 showed that five out of six scales scored above 0.7. The novelty scale scored a moderate reliability (alpha = 0.67), but it remained within acceptable limits. Conclusion: The E-KSPR Telemedicine application has strong potential for broader implementation as a digital innovation in maternal and child health services. Recommendation is to integrate E-KSPR Telemedicine with electronic medical record systems at healthcare facilities.